Socio-agrarian Conditions of Paddy Field in Sukabumi City - Hidayat Mansur, Yuda; Sutarto, Endriatmo (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2015)
Paddy field, the paddy planted area, is a very important land since it produces staple food – rice. Nevertheless, the contradictory condition occurs when agricultural land converted into non-agricultural land. Agricultural land that is not protected is proned to the land conversion, especially in urban areas or the growing city. The study aimed to figure out the strategies for protecting paddy field by identifying the spatial pattern of social quality of paddy field farmers. the research methodology used mixed concurent method by using qualitative and quantitative data and it was analized by cluster analysis. The research analysis used cluster analyisis in order to show the farmer similarity characteristics of each sub-districts. T h e resu lts sh o wed , th e fa rm er s’s so cia l rela t io n s g rou p is fo rm ed o f six typ e s co m m u n ity, n a m ely : (1 ) th e farmer owners, (2) the farmers owner also tenant, (3) the farmer owners concurrent collector (middlemen), (4) peasant (5) peasant also farm laborer, and (6) a laborer. Labor, farmers regeneration, and land tenure fragmentation influenced to land use change. The strategies can be implemented to protect sawah in S u kab u m i, n a m ely: (1 ) b y in crea sin g th e fa r m er’s a g rib u sin ess ca p a c ity, (2) Formulating the action plan for regenerating young farmers, (3) by controlling the permission regarded to change of land use, (4) Sukabumi municipal buys the productive ricefields. For further, It seem should be conducted assessment on studying of the study on the Agropolis and Agroedutourism concept in Sukabumi. Keyword: farmer community, paddy field protection strategy, social quality, sosio-agrarian PENDAHULUAN Latar Belakang Pendekatan pembangunan selama ini mengedepankan pada pembangunan yang berorientasi pada pertumbuhan ekonomi dengan mengesampingkan faktor-faktor sosial dan hal yang mendasar. Wiradi (2000) menyatakan bahwa pembangunan a la Orde Baru menganut paradigma modernisasi. Paradigma modernisasi bertumpu pada pandangan bahwa secara global, pembangunan itu terdiri dari empat proses, yaitu: (1) penanaman modal untuk meningkatkan produktivitas, (2) proses alih teknologi dari negara maju ke negara berkembang dalam rangka penerapan iptek bagi kegiatan produksi dan jasa, (3) proses munculnya negara-negara, dan organisasiorganisasi politik dan ekonomi skala besar, dan (4) proses urbanisasi (Wiradi 2000).